Respuesta:
p=6 , Q=5
Explicación paso a paso:
p=12 + (-1) × 2 + 2 × (-2)
p=12 - 2 + 2 × (-2)
p= 12 - 2 - 4
p=6
Q=4-[5+3(4-6)]
Q= 4[5 + 3 × (-2)]
Q=4-(5-6)
Q=4-(-1)
Q=4+1
Q=5
60
P= 12 - 2 ÷ -4
10 + 2
12
Q= 4 - [ 5 + 3(-2)]
4 - [5 - 6]
4 - [ -1 ]
4 + 1
5
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
p=6 , Q=5
Explicación paso a paso:
p=12 + (-1) × 2 + 2 × (-2)
p=12 - 2 + 2 × (-2)
p= 12 - 2 - 4
p=6
Q=4-[5+3(4-6)]
Q= 4[5 + 3 × (-2)]
Q=4-(5-6)
Q=4-(-1)
Q=4+1
Q=5
Respuesta:
60
Explicación paso a paso:
P= 12 - 2 ÷ -4
10 + 2
12
Q= 4 - [ 5 + 3(-2)]
4 - [5 - 6]
4 - [ -1 ]
4 + 1
5